Research skills within the frame of media and foreign language communication competence of students-journalists - Kydyrbay, K.K.; Frolova, G.M.; Kunakova, K.U.; Beikutova, A.M. (Karagandy University of the name of acad. E.A. Buketov, 2024)
In the article the formation and practical use of research skills were examined, which are considered one of the key skills of this foreign-language media and communicative competence of future journalists seeking a bachelor's degree. Citing domestic and foreign sources of information as examples, the authors suggest that developing research skills is best accomplished at the undergraduate level. The research skills of future journalists are important from the point of preparing oral scientific speech in accordance with the requirements of the communication rhetoric and academic ethics, as well as in order to be able to appropriately compose a scientific article and formulate questions during scientific conferences. Research skills need to be purposefully developed, which is what was done in the experimental part of this scientific work. The article presents a brief analysis of foreign language media communication competence, examines the process of developing the competencies of future journalists and highlights research skills. In conclusion, the authors present the results of an experiment conducted as part of their dissertation research. The experiment is presented in three stages, each of which is described in detail and analyzed in terms of the used methods’ effectiveness and their impact on the development of research skills among students.
In the article the formation and practical use of research skills were examined, which are considered one of the key skills of this foreign-language media and communicative competence of future journalists seeking a bachelor's degree. Citing domestic and foreign sources of information as examples, the authors suggest that developing research skills is best accomplished at the undergraduate level. The research skills of future journalists are important from the point of preparing oral scientific speech in accordance with the requirements of the communication rhetoric and academic ethics, as well as in order to be able to appropriately compose a scientific article and formulate questions during scientific conferences. Research skills need to be purposefully developed, which is what was done in the experimental part of this scientific work. The article presents a brief analysis of foreign language media communication competence, examines the process of developing the competencies of future journalists and highlights research skills. In conclusion, the authors present the results of an experiment conducted as part of their dissertation research. The experiment is presented in three stages, each of which is described in detail and analyzed in terms of the used methods’ effectiveness and their impact on the development of research skills among students.
Keywords: educational paradigm; media and foreign language communicative competence; mass media; future journalists; research skills; professionally oriented activity; кәсіби бағдарланған қызмет; білім беру парадигмасы; құзыреттілік тәсіл; медиа және шет тіліндегі коммуникативтік құзыреттілік; шет тіліндегі коммуникативтік құзыреттілік; медиа құзыреттілік; бұқаралық ақпарат құралдары; болашақ журналистер; зерттеу қабілеттері; профессионально-ориентированная деятельность; образовательная парадигма; компетентностный подход; медиа и иноязычная коммуникативная компетентность; средства массовой информации; будущие журналисты; исследовательские способности